Developing Plato_Pro: A Needs Analysis for Enhancing Self-Efficacy and Mathematics Learning in Sixth-Grade Proportional Problem Solving - Nurhafidoh, Lilik; Wiryanto, Wiryanto; Rahaju, Endah Budi (Journal of Innovation and Research in Primary Education, 2025)
This study aims to analyze the needs for developing Plato_Pro (Proportional Learning through Objects and Problems) instructional media in an effort to enhance self-efficacy and mathematics learning outcomes of sixth-grade elementary school students in proportional word problem tasks. The background of this research stems from students’ low ability to comprehend proportional word problems, particularly in determining the correct relationship between the given and unknown ratios. The study employed a descriptive qualitative approach supported by simple quantitative data, with participants consisting of 25 students from class VI-D of SD Negeri Sawotratap 1 and their mathematics teacher. Data were collected through classroom observations, interviews with teachers and students, as well as documentation of students’ learning outcomes. Data analysis followed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that most students still experience difficulties in solving proportional word problems due to limited conceptual understanding, weak reasoning ability, and the minimal use of concrete learning media. From the teachers’ perspective, limited skills in developing contextual learning media also posed a significant challenge. Therefore, there is a clear need to develop innovative instructional media such as Plato_Pro, which is designed based on concrete objects to facilitate conceptual understanding of proportion while supporting the enhancement of students’ self-efficacy and learning outcomes. These findings provide a foundation for further research focused on the development and empirical testing of Plato_Pro.